Алелопатія: ретроспективний погляд, сучасний стан та перспективи досліджень - Yurchak, L.D. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Evolution of development allelopathic direction in Ukraine and abroad, its present state and perspectives are presented.